2011
DOI: 10.1249/mss.0b013e31820c64ae
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Activity of the Peroneal Muscle after Foot Orthoses Therapy in Runners

Abstract: Enhanced muscle activation of the musculus peroneus longus in preactivation suggests an altered preprogrammed activity, which might lead to better ankle stability providing a possible mode of action for foot orthoses therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 42 publications
1
44
1
3
Order By: Relevance
“…This was interpreted as a change in motor program leading to better ankle stability. Eventually, this might point to a modified afferent input on the foot sole (or other proprioceptive structures), which leads to a change in muscular control [37]. This descriptive observation does not directly lead to a new `sensorimotor´ paradigm but it opens the field for new methodological approaches like the integration of neurophysiologic techniques like h-reflex measurements or transcranial magnetic stimulation (TMS) [38].…”
Section: Discussionmentioning
confidence: 99%
“…This was interpreted as a change in motor program leading to better ankle stability. Eventually, this might point to a modified afferent input on the foot sole (or other proprioceptive structures), which leads to a change in muscular control [37]. This descriptive observation does not directly lead to a new `sensorimotor´ paradigm but it opens the field for new methodological approaches like the integration of neurophysiologic techniques like h-reflex measurements or transcranial magnetic stimulation (TMS) [38].…”
Section: Discussionmentioning
confidence: 99%
“…27 Two studies assessed the activation of ankle muscles during running using electromyography. 28,29 Four studies consisted of kinematic analysis performed by a three-dimensional camera system [30][31][32][33] whereas a single study included a kinetic analysis performed on a force platform. 33 One study used an electronic platform system for assessment of foot type (Novel Electronics Munich, Germany); 34 and finally, one study measured the alignment of the lower limbs through measuring devices (tape and goniometer).…”
Section: ■ Resultsmentioning
confidence: 99%
“…11 Therefore, the functioning of shoes and foot orthoses may be mediated by an interplay of biomechanical and neuromuscular effects. 14,20 However, this theoretical framework is only speculative and far from conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants had not adapted to the SSFO condition. This may provide a reasonable explanation for these differences, because researchers 20,34 have suggested that a wearing period of at least 4 weeks is needed to see full adaptations to foot orthoses. Furthermore, the comfort scores for the SSFO condition were lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation